Lage, Maria Otília Pereira; Lage, Diana Maria Pereira Bessa (2016). Duas vezes água. Ilustrações de Helder Carvalho. Porto: [s.n.] - Topa , Francisco (CEM – Cultura, Espaço & Memória, 2023)
DOI: https://doi.org/10.21747/2182-1097/cem15r4